Pengaruh Implementasi Sistem Antrean Digital Terhadap Kepuasan Pasien pada Pelayanan Farmasi Puskesmas Cakranegara - Lalu Rusmika Apriwijaya; Irwan Hadi (Jaanur Elbarik Indonesia, 2026)
This study aimed to determine the impact of implementing a Digital Pharmacy Queueing System on patient satisfaction among those receiving pharmacy services at the Cakranegara Primary Health Center. A quantitative study using a one-group pre-test/post-test pre-experimental design was conducted, involving 100 patients receiving pharmacy services. Patient satisfaction was measured before and after the implementation of the Digital Pharmacy Queueing System using the Customer Satisfaction Score (CSAT) questionnaire. Data were analyzed using the Wilcoxon signed-rank test with a significance level of 0.05. The results showed that the implementation of the Digital Pharmacy Queueing System significantly increased patient satisfaction at the Cakranegara Primary Health Center pharmacy unit. The digitalization of pharmacy services is an effective strategy for enhancing service quality, operational efficiency, and patient-centered care in primary health facilities.